2009
DOI: 10.1007/s00455-009-9246-8
|View full text |Cite
|
Sign up to set email alerts
|

The Mayo Dysphagia Questionnaire-30: Documentation of Reliability and Validity of a Tool for Interventional Trials in Adults with Esophageal Disease

Abstract: The aim of this study was to develop the Mayo Dysphagia Questionnaire-30 Day (MDQ-30), a tool to measure esophageal dysphagia, by adapting items from validated instruments for use in clinical trials, and assess its feasibility, reproducibility, and concurrent validity. Outpatients referred to endoscopy for dysphagia or seen in a specialty clinic were recruited. Feasibility testing was done to identify problematic items. Reproducibility was measured by test-retest format. Concurrent validity reflects agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 16 publications
0
44
0
1
Order By: Relevance
“…The test-retest reliability data presented in present study demonstrated that the PedsQL™ EoE Module scales and summary scores did not change to a significant degree over an average interval of ~12 days between instrument administrations in pediatric patients with stable disease. In the adult dysphagia literature, the Mayo Dysphagia Questionnaire (MDQ) was found to be not responsive in a 14 day recall period, but rather performed better over a one month recall period (51). Additionally, there have been a number of responsiveness analyses with the PedsQL™ 4.0 Generic Core Scales in which the one month recall period was demonstrated to be sensitive to intervention effects (27).…”
Section: Discussionmentioning
confidence: 99%
“…The test-retest reliability data presented in present study demonstrated that the PedsQL™ EoE Module scales and summary scores did not change to a significant degree over an average interval of ~12 days between instrument administrations in pediatric patients with stable disease. In the adult dysphagia literature, the Mayo Dysphagia Questionnaire (MDQ) was found to be not responsive in a 14 day recall period, but rather performed better over a one month recall period (51). Additionally, there have been a number of responsiveness analyses with the PedsQL™ 4.0 Generic Core Scales in which the one month recall period was demonstrated to be sensitive to intervention effects (27).…”
Section: Discussionmentioning
confidence: 99%
“…A partial histologic response was >10 eosinophils / maximal hpf but less than half the immediate pretreatment eosinophil content. Secondary end points were: (1) changes in other histologic fi ndings (mast cell content or parabasal layer thickening), (2) the tempo of changes in these parameters on the elemental diet and aft er reintroducing normal food when the diet ended, and (3) improvement of dysphagia and other specifi c symptoms as scored by the Mayo Dysphagia Questionnaire-30 ( 11 ).…”
Section: Study End Pointsmentioning
confidence: 99%
“…Patient reported symptom severity and QoL were assessed using selected items from the Mayo Dysphagia Questionnaire-30 Day [8], the Swallowing Difficulty Index, the Swallowing Impact Scale, the MD Anderson Dysphagia Inventory [9], and the SF-12 Ò Questionnaire [10]. Items were selected based on face validity and relevance to patients performing self dilation.…”
Section: Methods Of Data Extractionmentioning
confidence: 99%